A theoretical dynamic model to study the vibration response characteristics of an axial piston pump. (March 2021) - Ye, Shaogan; Zhang, Junhui; Xu, Bing; Hou, Liang; Xiang, Jiawei; Tang, Hesheng
Graphical abstract: Highlights: A dynamic model of an axial piston pump is developed and experimentally validated. Influences of operating conditions on the vibrations are studied. Influences of stiffness and damping coefficients on the vibrations are studied. The amplitude-frequency vibration responses and phase trajectory plots are analyzed. Complex irregular motions occur under different working conditions. Abstract: A dynamic model with four masses and 19 degree of freedoms is proposed to investigate the vibration response characteristics of an axial piston pump. In the model, main parts are simplified by multiple lumped mass points connected with spring-damper elements. Experimental investigation is performed, and the discharge dynamic pressures and vibrations are measured to validate the dynamic model. Using the constructed model, influences of operating conditions (the discharge pressure, the rotational speed, and the displacement angle), and stiffness and damping coefficients between different contacting surfaces (the cylinder and valve plate, the piston and cylinder bore, and the slipper and swash plate) on the amplitude-frequency vibration responses and phase trajectory plots are analyzed. The findings showed that the vibration responses are significantly affected by the operating conditions, and are also considerably affected by the stiffness and damping coefficients. The rotational speed determines the fundamental frequency and its harmonics, and most of the harmonic vibration responses increase with increasing discharge pressure and displacement angle. The shape and the area defined by the phase trajectory are significantly changed by the operating conditions. The complex irregular motion might be changed into less irregular motion with decreasing discharge pressure, rotational speed and displacement angle.